SOLIDARITAS MEKANIK KOMUNITAS ISLAM DAN KRISTEN DI DESA KAMIJORO KECAMATAN BENER KABUPATEN PURWOREJO (Forum Ilmu Sosial, 2015)
Using qualitative method research, this study aims to discuss about the mechanical solidarity of Muslim and Christian communities in Kamijoro's village. Kamijoro community as a rural communities are multireligion, there are Islam and Christian communities. Kamijoro society does not make this distinction becomes a conflict. The differences of Kamijoro society religion unite by the perspective of Javanese society about all religion are good and the Javanese traditions are still preserved by the community in Kamijoro. It makes people in Kamijoro have a high sense of solidarity against the Christian community. The results show that religious differences does not become a barrier to unite, but a tool to improve of solidarity within society of the Islamic community and the Christian community.